Protective Effects of Geraniol on Long Term Renal Ischemia/Reperfusion Injury in Rats - Can,Senanur (2019)
Abstract Possible protective effects of geraniol, known as antioxidant properties, were analyzed biochemically and histologically on experimental long-term renal ischemia/reperfusion I/R injury in rats. This study used 3-4 months old male Wistar albino rats and were divided into 4 groups (n = 7) by random selection: Group I (Sham Group), Group II (I/R+SF), Group III (I/R+50 mg/kg geraniol), and Group IV (I/R+100 mg/kg geraniol). A right nephrectomy was performed in all groups under anesthesia. Groups I and II were inoculated with SF (1 ml/kg) and Groups III and IV were inoculated with 50 mg/kg and 100 mg/kg of geraniol, injected intraperitoneally. For Groups II, III, and IV, I/R durations were determined to be 60 mins ischemia and 24 hours reperfusion. At the end of the experiment, Urea (BUN), Creatinine (CRE) activities in the blood serum and the catalase (CAT), glutathione peroxidase (GPx) and Superoxide dismutases (SOD), enzyme activities in kidney tissue were measured. Histologic sections were examined by light microscopy using Hematoxylin & Eosine. As a result, it was determined that 100 mg / kg geraniol against renal I/R injury shows more antioxidant effect and protection than 50 mg / kg geraniol.